Demographics of Pediatric Orbital Lesions: A Tertiary Eye Center Experience in Saudi Arabia - Hind Manaa Alkatan; Faisal Al Marek; Sahar Elkhamary (Springer, 2019)
Orbital lesions vary in their classification, incidence, and presentation depending on the age and geographic distribution. Such lesions in the pediatric age group have been studied extensively because of the possibility of faster progression of orbital involvement and the higher risk of morbidity in this age group in which vision is still developing. In Saudi Arabia, orbital lesions were studied over a 6-year period in the late 1980s, when retinoblastoma cases used to present late with orbital involvement. In this study, we revisited the same topic 20 years later aiming to find out the most recent prevalence of orbital lesions in a similar population of patients over a longer period (14 years) in the same eye center, and compare the current results to other reports worldwide. A total of 107 lesions from 106 patients were identified by tissue diagnosis, of which more than half of the lesions were benign cystic (being the most common), vasculogenic, and inflammatory in 63% [95% confidence interval (CI, 53.3-72.0)] of all biopsied lesions. Neoplasms accounted for 37% [95% CI (28.0-45.8)] with rhabdomyosarcoma being the most common, accounting for about one third of neoplasms, and no orbital cases of retinoblastoma were found. Our results demonstrated different distribution of orbital lesions in recent years reflecting the indirect effect of the improved health awareness and medical care in Saudi Arabia. This baseline demographic study is expected to be helpful for further clinical and prognostic studies with emphasis on pediatric orbital malignant lesions, their clinical presentation, management, and prognosis.